2007
DOI: 10.1017/s0022215107009942
|View full text |Cite
|
Sign up to set email alerts
|

Five-year results for use of single-flanged tympanostomy tubes in children

Abstract: We found that 36.4 per cent of the tubes had extruded within 12 months and 71.0 per cent within 24 months. Results showed that 14.1 per cent of the tubes had been removed because of prolonged retention, with a mean time to removal of 38.9 months. The time to extrusion was longer and the rate of retained tubes was higher than those reported for several other short-term tubes. We found that 4.5 per cent of tube insertions had resulted in a persistent perforation, a higher percentage than previously reported for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Knutsson and von Unge 77 retrospectively reviewed the medical records of 348 patients (640 tubes) who underwent tympanostomy tube insertion with short‐term single‐flanged fluoroplastic tubes for OME (75.4%), rAOM (20.2%), or retraction pathology (4.4%). By 12 months, 36.4% and by 24 months, 71.0% of tubes were extruded.…”
Section: Discussionmentioning
confidence: 99%
“…Knutsson and von Unge 77 retrospectively reviewed the medical records of 348 patients (640 tubes) who underwent tympanostomy tube insertion with short‐term single‐flanged fluoroplastic tubes for OME (75.4%), rAOM (20.2%), or retraction pathology (4.4%). By 12 months, 36.4% and by 24 months, 71.0% of tubes were extruded.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its sub-millimeter dimensions and high flexibility [20], SEE could be inserted into the middle ear through a small incision in the tympanic membrane, such as routinely introduced for the placement of tympanostomy tubes [30, 31]. While inside the middle ear, SEE could not only image the stapes in three dimensions [21], but it could also map the frequency response of the footplate, which provides an indication on the function of the ossicles.…”
Section: Discussionmentioning
confidence: 99%
“…8-14 months) has been reported in the literature. Previously reported rates of persistent TMPs in patients after long-term VT treatment ranged between 10 and 30% [27][28][29][30][31][32][33][34][35][36]. Based on this clinical observation, our research group embarked on a rat study and found that chronic TMPs staying patent for up to 10 weeks were successfully created by VT treatment only.…”
Section: Introductionmentioning
confidence: 91%